'Water Has Aroused the Girls' Hearts': Gendering Water and Soil Conservation in 1950s China. Issue 1 (29th September 2021) - Muscolino, Micah S
Abstract: Water and soil conservation in the village of Dengjiabao in Gansu province, north-west China, gained nationwide renown through state-led campaigns against erosion during the 1950s. This was deeply interconnected with shifting conceptions of women's work and had far-reaching effects on their everyday lives. Investigation of these conservation programmes adds to recent efforts to integrate gender and environmental history. Since the gendered division of labour in rural China dictated that women should do the work of acquiring fuel and water, measures that conserved these resources brought genuine improvements for them. They also reshaped local marriage patterns by making previously resource-starved villages more attractive to young women from other areas. However, a dissonance existed between the official propaganda and the experience of conservation for rural women. Oral history interviews and archival documents show that balancing the demands of conservation work with household responsibilities intensified the pressures placed upon women. Mobilization for the highly militarized conservation campaigns that were an integral part of the Great Leap Forward (1958–61), and the famine they helped to precipitate, subjected women to unprecedented burdens that affected their domestic lives and had an enduring effect on their health and well-being.